Вы находитесь на странице: 1из 8

4

DIFFERENTIAL EQUATIONS

4.1: CONSTRUCT THE DIFFERENTIAL EQUATIONS

4.1.1: Identify Type Of Differential Equations

 Order → The number of the highest derivative in a differential equation. A differential equation of order 1 is called first order; order 2
second order, etc.
Example:

dy 1 x
i.  → first order differential equation
dx 1  y 2

dy
ii. x2  y sin x → first order differential equation
dx

d2y dy
iii. 2
4  2 y  x 2 → second order differential equation
dx dx

 Degree → The power of the highest order derivative in


the equation. A differential equation of degree is called first degree, second degree, etc.
Example:

dy
i. xy  xy 2  x → first order differential equation with first degree.
dx

2
 dy 
ii. y 2  1  x  → first order differential equation with second degree.
 dx 

2
d2y
iii.    2 dy  10 y  cos 2 x → second order differential equation with second degree.
 dx 2  dx
 

Try this!

Determine order and degree for below equations:

2
 dy  4 x
a)   
 dx  x3
ds
b) t2  sin t  0
dt
d2y dy
c) x 2
4  2 xy  0
dx dx
2
d2y
d)    3 dy  2 y  0
 dx 2  dx
 

48
4.1.2: Construct The Differential Equation

 Example (a):
Construct the differential equation for y = A sin 2x

Solution:

Step 1: Write down the question as the 1st equation

y = A sin 2x 1

𝒅𝒚
Step 2: Differentiate for the 1st equation (make it as 2nd equation)
𝒅𝒙

y = A sin 2x
𝑑𝑦
= 2A cos 2x 2
𝑑𝑥

Step 3: For the 3rd equation, properly arrange the constant.

𝑑𝑦
= 2A cos 2x
𝑑𝑥
1 𝑑𝑦
𝐴 = 2 cos 2𝑥 (𝑑𝑥 ) 3

Step 4: Substitute 3rd equation into 1st equation and simplify the final calculation.

y = A sin 2x

1 𝑑𝑦
𝑦 = 2 cos 2𝑥 (𝑑𝑥 ) sin 2𝑥

sin 2𝑥 𝑑𝑦
𝑦= ( )
2 cos 2𝑥 𝑑𝑥

1 𝑑𝑦
𝑦 = 2 tan 2𝑥 (𝑑𝑥 )

𝑑𝑦
2𝑦 = tan 2𝑥 ( )
𝑑𝑥

𝑑𝑦 2𝑦
𝑑𝑥
= tan 2𝑥 First order differential equation

 Example (b):
Construct the differential equation for y = Cx3 + x4

Solution:

Step 1: y = Cx3 + x4
1
𝑑𝑦
Step 2: = 3Cx2 + 4x3 2
𝑑𝑥

𝑑𝑦⁄ 3
𝑑𝑥 −4𝑥 3
Step 3: 𝐶= 3𝑥 2

49
Step 4: y = Cx3 + x4

𝑑𝑦⁄ 3
𝑑𝑥 −4𝑥
𝑦=( 3𝑥 2 ) 𝑥3 + 𝑥4

𝑥 𝑑𝑦 𝑥
= 3 (𝑑𝑥 ) − 3 (4𝑥 3 ) + 𝑥 4

𝑥 𝑑𝑦 𝑥4
= 3 (𝑑𝑥 ) − 3

𝑑𝑦 3𝑦+𝑥 4
𝑑𝑥
= 𝑥
First order
differential equation

 Example (c):
Construct the differential equation for y = Ax2 – Bx + x

Solution:

Step 1: Write down the question as the 1st equation

y = Ax2 – Bx + x 1

𝒅𝒚
Step 2: Differentiate for the 1st equation (make it as 2nd equation).
𝒅𝒙

y = Ax2 – Bx + x
𝑑𝑦
= 2Ax – B + 1 2
𝑑𝑥

Step 3: If the differentiation still have 2 constants, do the second order differentiation (make it as 3rd equation).

𝑑2 𝑦
= 2𝐴 3
𝑑𝑥 2

Step 4: For the 3rd equation, properly arrange the constant (make it as 4th equation).

𝑑2 𝑦
𝑑𝑥 2
= 2𝐴
1 𝑑2 𝑦
( )
2 𝑑𝑥 2
=𝐴 4

Step 4: Substitute 4th equation into 2nd equation.

𝑑𝑦
= 2Ax – B + 1
𝑑𝑥

𝑑𝑦 1 𝑑2 𝑦
= 2 [( ) ( )] 𝑥 −𝐵+1
𝑑𝑥 2 𝑑𝑥 2

𝑑𝑦 2𝑥 𝑑2 𝑦
𝑑𝑥
= ( 2 ) (𝑑𝑥 2 ) − 𝐵 + 1

Step 5: Arrange the second constant properly (make it as 5th equation).


2
2𝑥 𝑑 𝑦 𝑑𝑦
𝐵 = ( )( )− +1
2 𝑑𝑥2 𝑑𝑥

2
𝑑 𝑦 𝑑𝑦
𝐵 = 𝑥( )− +1 5
𝑑𝑥2 𝑑𝑥

50
Step 6: Substitute both 4th and 5th equation into 1st equation.
y = Ax2 – Bx + x

2 2
1 𝑑 𝑦 𝑑 𝑦 𝑑𝑦
𝑦=[ ( )] 𝑥2 − [𝑥 ( 2 ) − + 1] 𝑥 + 𝑥
2 𝑑𝑥2 𝑑𝑥 𝑑𝑥

𝑥 2 𝑑2 𝑦 𝑑2𝑦 𝑑𝑦
= ( )− (𝑥 2 ) ( )+ (𝑥) ( ) − 𝑥 + 𝑥
2 𝑑𝑥 2 𝑑𝑥 2 𝑑𝑥

𝑥2 𝑑2 𝑦 𝑑𝑦
= 2
− (𝑥 2 ) (𝑑𝑥 2 ) + (𝑥) (𝑑𝑥 )

𝑥 2 𝑑2 𝑦 𝑑𝑦
𝑦=− ( )+ (𝑥) ( )
2 𝑑𝑥 2 𝑑𝑥

Second order differential equation

Try this!

Construct the differential equation for:

a) y = A cos x + B sin x

b) y = Ax2 + 3

c) y2 = 5Ax

d) y = Dx2 + Ex

4.2: FIRST ORDER DIFFERENTIAL EQUATIONS

 There are 4 types of first order differential equations:


o Direct integration
o Separable variables
o Homogenous equation
o Linear equation (integrating factors)

4.2.1: Direct Integration


𝑑𝑦
 Form of = 𝑓(𝑥)
𝑑𝑥

 Example (d):

Solve below differential equation

𝑑𝑦
𝑑𝑥
= 7𝑥 2 − 8𝑥 2 + 7

Solution:

Step 1: Solve using direct integration

𝑑𝑦
𝑑𝑥
= 7𝑥 2 − 8𝑥 2 + 7
∫ 𝑑𝑦 = ∫(7𝑥 2 − 8𝑥 2 + 7)𝑑𝑥
7𝑥 6 8𝑥 3
𝑦= − + 7𝑥 + 𝑐
6 3
51
4.2.2: Separable Variables

𝑑𝑦
 Form of = 𝑓(𝑥)ℎ(𝑦)
𝑑𝑥

𝑑𝑦 𝑓(𝑥)
=
𝑑𝑥 ℎ(𝑦)

 Example (e):

Solve below differential equation

𝑑𝑦
𝑠𝑒𝑐 2 𝑦 = 𝑠𝑒𝑐 2 𝑥
𝑑𝑥

Solution:

Step 1: Separate two variables with ‘x’ on the right and ‘y’ on the left.

𝑑𝑦
𝑠𝑒𝑐 2 𝑦 = 𝑠𝑒𝑐 2 𝑥
𝑑𝑥
𝑑𝑦
∫ 𝑠𝑒𝑐 2 𝑦 𝑑𝑥 = ∫ 𝑠𝑒𝑐 2 𝑥 𝑑𝑥

Step 2: Solve the integral

𝑑𝑦
∫ 𝑠𝑒𝑐 2 𝑦 𝑑𝑥 = ∫ 𝑠𝑒𝑐 2 𝑥 𝑑𝑥

tan y = tan x + c

4.2.3: Homogenous Equation

 Form of substitution 𝑦 = 𝑣𝑥
 Example (f):
Solve below differential equation

𝑑𝑦
(𝑥 2 + 𝑥𝑦) = 𝑥𝑦 − 𝑦 2
𝑑𝑥

Solution:

Step 1: Separate the equation

𝑑𝑦 𝑥𝑦−𝑦 2
𝑑𝑥
= 𝑥 2 +𝑥𝑦 1

Step 2: Substitution 𝑦 = 𝑣𝑥
𝑦 = 𝑣𝑥 2
𝑑𝑦 𝑑𝑣
𝑑𝑥
= 𝑣 + 𝑥 (𝑑𝑥) 3

Step 3: Substitute 3rd equation into 1st equation

𝑑𝑣 𝑥𝑦−𝑦 2
𝑣 + 𝑥 (𝑑𝑥) = 𝑥 2 +𝑥𝑦

52
Step 4: Replace 2nd equation into Step 3
𝑑𝑣 𝑥(𝑣𝑥)−(𝑣𝑥)2
𝑣 + 𝑥 (𝑑𝑥) = 𝑥 2 +𝑥(𝑣𝑥)

𝑥 2 (𝑣−𝑣 2 )
=
𝑥 2 (1+𝑣)

𝑑𝑣 𝑣−𝑣 2
𝑥 𝑑𝑥 = ( 1+𝑣 ) − 𝑣

𝑣−𝑣 2 −(𝑣+𝑣 2 )
= 1+𝑣

𝑑𝑣 −2𝑣 2
𝑥 𝑑𝑥 = 1+𝑣

Step 5: Separate the variables with ‘x’ and ‘v’ on different sides
𝑑𝑣 −2𝑣 2
𝑥 =
𝑑𝑥 1+𝑣

1+𝑣 1
∫ −2𝑣2 𝑑𝑣 = ∫ 𝑥 𝑑𝑥

Step 6: Solve the integral

1 1+𝑣 1
− ∫ 𝑑𝑣 = ∫ 𝑑𝑥
2 𝑣2 𝑥

1 1 𝑣 1
− 2 ∫ 𝑣 2 + 𝑣 2 𝑑𝑣 = ∫ 𝑥 𝑑𝑥

1 1 1
− 2 ∫ 𝑣 −2 + 𝑣 𝑑𝑣 = ∫ 𝑥 𝑑𝑥

1 𝑣 −1
− 2 [ −1 + ln 𝑣] = ln 𝑥 + 𝑐

1
− [−𝑣 −1 + ln 𝑣] = ln 𝑥 + 𝑐
2

Step 7: Replace 𝑦 = 𝑣𝑥

1 𝑥 𝑦
− 2 [− 𝑦 + ln (𝑥 )] = ln 𝑥 + 𝑐

53
4.2.4: Linear Equation (Integrating Factors)

𝑑𝑦
 Form of + 𝑃𝑦 = 𝑄
𝑑𝑥

𝑦 ∙ 𝐹𝑃 = ∫ 𝑄 ∙ 𝐹𝑃 𝑑𝑥 with 𝐹𝑃 = 𝑒 ∫ 𝑃 𝑑𝑥

 Example (g):
Solve below differential equation

𝑑𝑦 3
(𝑥 − 2)
𝑑𝑥
−𝑦 = (𝑥 − 2)

Solution:

𝑑𝑦
Step 1: Simplify
𝑑𝑥

𝑥−2 𝑑𝑦 𝑦 (𝑥−2)3
( ) − (𝑥−2)
𝑥−2 𝑑𝑥
= 𝑥−2

𝑑𝑦 𝑦
𝑑𝑥
− (𝑥−2) = (𝑥 − 2)2

𝑑𝑦 1
𝑑𝑥
− 𝑦 (𝑥−2) = (𝑥 − 2)2

Step 2: Identify P and Q

1
𝑃=− 𝑄 = (𝑥 − 2)2
𝑥−2

Step 3: Integrating factor of P

𝐹𝑃 = 𝑒 ∫ 𝑃 𝑑𝑥
1
= 𝑒 ∫ −𝑥−2 𝑑𝑥
= 𝑒 −ln(𝑥−2)

−1
∴ 𝑒 −ln(𝑥−2) = 𝑒 ln(𝑥−2)

𝑒 ln 𝐹 = 𝐹 -ln x = ln x-1

e-ln (x-2) = e(x-2)-1


eln F = F
= (x-2)-1
1
FP =
𝑥−2

54
Step 4: Substitute into equation

𝑦 ∙ 𝐹𝑃 = ∫ 𝑄 ∙ 𝐹𝑃 𝑑𝑥

1 1
𝒚•
𝑥−2
= ∫(𝑥 − 2) • 𝑥−2 𝑑𝑥
1
𝒚•
𝑥−2
= ∫(𝑥 − 2)

Step 5: Solve the integral

1
𝒚• = ∫(𝑥 − 2)
𝑥−2

1 𝑥2
𝒚• = − 2𝑥 + 𝑐
𝑥−2 2

Step 6: Simplify ‘y’


1 𝑥2
𝑦• = − 2𝑥 + 𝑐
𝑥−2 2

1 𝑥2
(𝑥 − 2)𝑦 • = (𝑥 − 2) − 2𝑥(𝑥 − 2) + 𝑐(𝑥 − 2)
𝑥−2 2

𝑥3 2𝑥 2
𝑦= − − 2𝑥 2 + 4𝑥 + 𝑐(𝑥 − 2)
2 2

𝑥3
𝑦= − 3𝑥 2 + 4𝑥 + 𝑐(𝑥 − 2)
2

Try this!

Solve below differential equation:

𝑑𝑦
a) 𝑥 ( ) = (1 + 𝑥 3 )𝑦 2
𝑑𝑥

𝑑𝑦
b) (3𝑥 + 2) ( ) + 4𝑦 = (3𝑥 + 2)2
𝑑𝑥

𝑑𝑦 𝑦 2 +𝑥𝑦 2
c) ( )=
𝑑𝑥 𝑥 2 𝑦−𝑥 2

𝑑𝑦
d) 𝑥 ( ) + 𝑦 = 𝑥3
𝑑𝑥

55